PERCERAIAN YANG DISEBABKAN SALAH SATU PASANGAN PINDAH AGAMA DI PENGADILAN NEGERI BANDUNG - Wiwin Putra, Joni Zulhendra dan (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Marriage cannot be separated from the religious aspect, especially when the Marriage Law emphasizes the importance of the religious aspect in the conditions for the validity of a marriage as regulated in Article 2 paragraph (1)